Combined MLH1/MSH2/MSH6 assessment by immunohistochemistry and RT-qPCR: analytical agreement and added value for pathological risk stratification in colorectal cancer - Zhang, Yi; Li, Xin; Ran, Jing; Zuo, Ningchuang (Journal of Medical Biochemistry, 2026)
Background: Mismatch repair (MMR) status is routinely assessed in colorectal cancer (CRC), yet the laboratory value of combining multiple MMR targets across platforms for risk stratification requires verification under real-world testing conditions. This study evaluated MLH1, MSH2 and MSH6 using immunohistochemistry (IHC) and RT-qPCR in resection specimens and quantified the added value of combined assessment for stratifying tumor invasion and lymph node status.Methods: FFPE tumor tissue and paired adjacent non-tumor tissue were collected from patients undergoing radical resection (April 2024–June 2025). IHC was interpreted using internal positive controls and a predefined dichotomous rule (retained vs complete loss in tumor nuclei). RT-qPCR assays were performed with batch-level controls, non-template controls, and replicate measurements; acceptance criteria were prespecified. Agreement between readers and between platforms was assessed. Multivariable logistic models were used to evaluate discrimination for advanced invasion and node-positive disease, with internal validation and calibration assessment.Results: MLH1, MSH2 and MSH6 were reduced in tumor tissue compared with adjacent tissue at both protein and mRNA levels. Lower MMR expression was associated with more advanced invasion and positive nodal status. A combined model incorporating MLH1/MSH2/MSH6 improved discrimination compared with single markers. Quality control metrics supported the feasibility of the combined workflow in routine laboratory settings.Conclusions: A combined MLH1/MSH2/MSH6 testing strategy integrating IHC and RT-qPCR provides measurable incremental value for pathological risk stratification in CRC when implemented with standardized interpretation and quality control.
Keywords: Colorectal cancer; MLH1; MSH2; MSH6; mismatch repair; clinicopathological features; diagnostic value